Effect of rurality and of human capital resources in the entrepreneurial opportunity identification process - Kedmenec, Irena (Naše gospodarstvo, 2015)
In this paper, based on the country study of Slovenia, we tried to answer the question why individuals in rural residential areas are less likely to recognize entrepreneurial opportunities. Our results show that the increase in resources in human capital consisting of education, skills, knowledge and experiences for entrepreneurship, has a significant and positive effect on opportunity identification. For the policy creators, our results suggest that the policies focused on the entrepreneurial education, especially the education that would enable the acquisition of real-life entrepreneurial experiences and skills are useful, especially in rural areas.
Keywords: podeželje; rural area; podjetništvo; viri; podjetniki; poslovno tveganje; education; izobraževanje